Numerical Investigation into the Effect of Damage Openings on Ship Hydrodynamics by the Overset Mesh Technique - Xinlong Zhang; Zhuang Lin; Simone Mancini; Ping Li; Dengke Liu; Fei Liu; Zhanwei Pang (Journal of Marine Science and Engineering, 2019)
Damage stability is difficult to assess due to the complex hydrodynamic phenomena regarding interactions between fluid and structures. Therefore, a detailed analysis of the flooding progression and motion responses is important for improving ship safety. In this paper, numerical simulations are performed on the damaged DTMB 5415 ship at zero speed. All calculation are carried out using CD Adapco Star CCM + software, investigating the effect of damage openings on ship hydrodynamics, including the side damage and the bottom damage. The computational domain is modelled by the overset mesh and solved using the unsteady Reynold-average Navier-Stokes (URANS) solver. An implicit solver is used to find the field of all hydrodynamics unknown quantities, in conjunction with an iterative solver to solve each time step. The Volume of Fluid (VOF) method is applied to visualize the flooding process and capture the complex hydrodynamics behaviors. The simulation results indicated that two damage locations produce the characteristic flooding processes, and the motion responses corresponding to the hydrodynamic behaviors are different. Through comparative analysis, due to the difference between the horizontal impact on the longitudinal bulkhead and the vertical impact on the bottom plate, the bottom damage scenario always has a larger heel angle than the side damage scenario in the same period. However, the pitch motions are basically consistent. Generally, the visualization of the flooding process is efficient to explain the causes of the motion responses. Also, when the damage occurs, regardless of the bottom damage or the side damage, the excessive heel angle due to asymmetric flooding is often a threat to ship survivability with respect to the pitch angle.

Cloning and expression analysis of the StCUL1 gene in potato - Peng-Xiang Pang; Li Shi; Xiao-Juan Wang; Yan-Nan Chang; Yong-Ping Luo; Jin-Lin Feng; Hemu Eri; Gang Gao (Journal of Plant Biochemistry and Biotechnology, 2019)

Potential role of IL-37 signaling pathway in feedback regulation of autoimmune Hashimoto thyroiditis - Cui-Ping Ren; Li Sun; Feng-Chun Liu; Chun-Lin Zuo; Miao Liu; Wenda Gao; Ji-Jia Shen (Histochemistry and Cell Biology, 2019)

Numerical Investigation on the Scale Effect of a Stepped Planing Hull - Lei Du; Zhuang Lin; Yi Jiang; Ping Li; Yue Dong (Journal of Marine Science and Engineering, 2019)
This article discusses the scale effects on a planing boat, utilizing the computational fluid dynamics method. The simulation is compared with a tank test for verification and validation. The planing boat sails use both aerodynamics and hydrodynamics. Studying the performances and wave patterns of different dimensions of the models is the best way to investigate the scale effect without using experimental data. The resistance is discussed in two parts, namely residuary resistance and friction resistance, and is compared to the calculated data using the international towing tank conference (ITTC) formula. The computational fluid dynamics (CFD) calculations of the model are increased by 4.77% on average, and the boat computations are also increased by 3.57%. The computation shows the scale effect in detail. The residuary resistance coefficients at different scales are approximately equal, and the friction resistance coefficients show the scale effect. The scale effect for longitudinal steadiness is also captured for the period of the porpoising behavior. The rational for the full-scaled boat oscillation period and the model is the root of the scales.

Gastrodin ameliorates microvascular reperfusion injury–induced pyroptosis by regulating the NLRP3/caspase-1 pathway - Wenjing Sun; Hongquan Lu; Lechun Lyu; Ping Yang; Zhi Lin; Ling Li; Lin Sun; Di Lu (Journal of Physiology and Biochemistry, 2019)

Excess copper effects on growth, uptake of water and nutrients, carbohydrates, and PSII photochemistry revealed by OJIP transients in Citrus seedlings - Qiang Li; Huan-Huan Chen; Yi-Ping Qi; Xin Ye; Lin-Tong Yang; Zeng-Rong Huang; Li-Song Chen (Environmental Science and Pollution Research, 2019)

Mechanism of dry detoxification of chromium slag by carbon monoxide - Liwei He; Bin Li; Zhang Lin; Ping Ning; Zhuang Shen (Environmental Chemistry Letters, 2019)

Assessment of slope construction risk uncertainty based on index importance ranking - Daming Lin; Ping Chen; Jilei Ma; Yun Zhao; Tao Xie; Renmao Yuan; Lin Li (Bulletin of Engineering Geology and the Environment, 2019)

Morphological and Genetic Characterization of the Poorly Known Species Subulura chinensis Schwartz, 1926 (Nematoda: Ascaridida) from Athene noctua (Scopoli) (Strigiformes: Strigidae) - Ning Guo; Lu-Ping Zhang; Lin-Wei Li; Liang Li (Acta Parasitologica, 2019)

Extreme stress threatened double rice production in Southern China during 1981–2010 - Sheng-Li Liu; Xing Wang; Shou-Tian Ma; Xin Zhao; Fu Chen; Xiao-Ping Xiao; Rattan Lal; Hai-Lin Zhang (Theoretical and Applied Climatology, 2019)

Comparative Transcriptome Analysis Reveals Differentially Expressed Genes and Signaling Pathways Between Male and Female Red-Tail Catfish (Mystus wyckioides) - Jun-Jie Wu; Yu-Lin Zhou; Zhong-Wei Wang; Guang-Hua Li; Fang-Peng Jin; Li-Li Cui; Hai-Tao Gao; Xin-Ping Li; Li Zhou; Jian-Fang Gui (Marine Biotechnology, 2019)

F‐box proteins MoFwd1, MoCdc4 and MoFbx15 regulate development and pathogenicity in the rice blast fungus Magnaporthe oryzae - Huan‐Bin Shi; Nan Chen; Xue‐Ming Zhu; Shuang Liang; Lin Li; Jiao‐Yu Wang; Jian‐Ping Lu; Fu‐Cheng Lin; Xiao‐Hong Liu (Environmental Microbiology, 2019)
Summary The Skp1‐Cul1‐F‐box‐protein (SCF) ubiquitin ligases are important parts of the ubiquitin system controlling many cellular biological processes in eukaryotes. However, the roles of SCF ubiquitin ligases remain unclear in phytopathogenic Magnaporthe oryzae . Here, we cloned 24 F‐box proteins and confirmed that 17 proteins could interact with MoSkp1, showing their potential to participate in SCF complexes. To determine their functions, null mutants of 21 F‐box‐containing genes were created. Among them, the F‐box proteins MoFwd1, MoCdc4 and MoFbx15 were found to be required for growth, development and full virulence. Fluorescent‐microscopy observations demonstrated that both MoFbx15 and MoCdc4 were localized to the nucleus, compared with MoFwd1, which was distributed in the cytosol. MoCdc4 and MoFwd1 bound to MoSkp1 via the F‐box domain, the deletion of which abrogated their function. Race tube and qRT‐PCR assays confirmed that MoFwd1 was involved in circadian rhythm by regulating transcription and protein stability of the core circadian clock regulator MoFRQ . Moreover, MoFWD1 also orchestrates conidial germination by influencing conidial amino acids pools and oxidative stress release. Overall, our results indicate that SCF ubiquitin ligases play indispensable roles in development and pathogenicity in M. oryzae .

A Numerical Investigation on the Flooding Process of Multiple Compartments Based on the Volume of Fluid Method - XinLong Zhang; Zhuang Lin; Simone Mancini; Ping Li; Ze Li; Fei Liu (Journal of Marine Science and Engineering, 2019)
A detailed description of the flooding process is crucial to analyze the complex hydrodynamic behaviors and enhance the survivability of the damaged ship. In this paper, through establishing three typical damage scenarios with various locations, the commercial software CD Adapco STAR-CCM+ based on the Reynolds-Averaged Navier-Stokes (RANS) solver is applied to simulate the flooding process involving multiple compartments. The basic computational fluid dynamics (CFD) models and specific simulation settings are elaborated. The volume of fluid (VOF) method combined with the user defined field function is developed to distribute the initial free surface. The captured flooding process indicates that the air compression due to the restricted ventilation decreases the flooding amount. The obtained flooding time can provide necessary data to support for appropriate rescue management and evacuation options.

Evaluation of the integrated multi-satellite retrievals for global precipitation measurement over the Tibetan Plateau - Lu Ma; Lin Zhao; Li-ming Tian; Li-ming Yuan; Yao Xiao; Le-le Zhang; De-fu Zou; Yong-ping Qiao (Journal of Mountain Science, 2019)

High Circulatory Phosphate Level Is Associated with Cerebral Small-Vessel Diseases - Chih-Ping Chung; Li-Ning Peng; Kun-Hsien Chou; Li-Kuo Liu; Wei-Ju Lee; Ching-Po Lin; Liang-Kung Chen; Pei-Ning Wang (Translational Stroke Research, 2019)

Favus of Scrotum Due to Trichophyton rubrum in Immunocompetent Patients: A Clinical, Mycological and Ultrastructural Study - Ze-Hu Liu; Xiu-Jiao Xia; Yong Zhang; Yan Zhong; Bo Sang; Qiu-Ping Li; Mei Wang; Wen-Wen Lv; Hui-Lin Zhi; Xiang-Dong Wang; Cui-Ping Guan; Hong Shen (Mycopathologia, 2019)

Influence of permeation effect on the microfabric of the slip zone soils: A case study from the Huangtupo landslide - Fa-sheng Miao; Yi-ping Wu; Yuan-hua Xie; Lin-wei Li; Jie Li; Lei Huang (Journal of Mountain Science, 2019)

Short-day treatment affects growth, physiological parameters and needle proteome of Chinese pine (Pinus tabuliformis Carr.) seedlings - Le Jiang; R. Kasten Dumroese; Yong Liu; Guolei Li; Ping Lin (New Forests, 2019)

Gene structure, recombinant expression and function characterization of Siniperca chuatsi Fsrp‐3 - Jianhua Wang; Jia Cheng; Yulong Li; Huiling Yan; Ping Wu; Xin Zhu; Li Liu; Lin Chen; Wuying Chu; Jianshe Zhang (Journal of Fish Biology, 2019)
A full‐length complementary (c)DNA sequence encoding follistatin‐related protein 3 ( fsrp‐3 ) was determined from skeletal muscle in Chinese mandarin fish Siniperca chuatsi , its molecular structure was characterised and its function suggested. The putative structure of S. chuatsi Fsrp‐3 contains an N‐terminal domain and two follistatin domains. Quantitative reverse‐transcription (qRT)‐PCR assays revealed that fsrp‐3 messenger (m)RNA was differentially expressed among assayed tissues and was highly expressed in heart and intestine. fsrp‐3 mRNA exhibited increasing expression from the larval to the juvenile stage (500 g). To investigate the potential function of S. chuatsi fsrp‐3 in muscle growth, we constructed a Fsrp‐3 prokaryotic expression system and injected the purified Fsrp‐3 fusion protein into the dorsal muscle. Fsrp‐3 administration significantly influenced cross‐section area, satellite cell activation frequency and nuclear density of S. chuatsi muscle fibres. Following Fsrp‐3 treatment, the expression of myogenic regulatory factors was up‐regulated and decline in the expression of myostatin was observed. The study revealed that Fsrp‐3 may affect muscle growth by regulating myogenic regulatory factor expression and antagonizing myostatin function to initiate satellite cell activation and differentiation in S. chuatsi .

Sulfide Rb-Sr and Zircon U-Pb Dating of the ~825 Ma Liujiaping Cu-Zn deposit in the Northwestern Yangtze Block (China) and its tectonic implications - Yan-Ping Su; Bao-Lin Zhang; Hui-Zhong Li; Ya-Na Miao; Xiao-Li Shen (International Geology Review, 2019)

Expression of the intrarenal angiotensin receptor and the role of renin-angiotensin system inhibitors in IgA nephropathy - Zheng Zhang; Shi-min Jiang; Ye-ping Ma; Pei-lin Dai; Yi-ning Wang; Gu-ming Zou; Hong-mei Gao; Yue Yang; Wen-ge Li (Molecular and Cellular Biochemistry, 2019)

Pond-bottom decomposition of leaf litters canopied by free-floating vegetation - Ya-Lin Zhang; Hong-Bin Li; Li Xu; Xu Pan; Wen-Bing Li; Jian Liu; Yue-Ping Jiang; Yao-Bin Song; Ming Dong (Environmental Science and Pollution Research, 2019)

Attribute recognition model for risk assessment of water inrush - Jing Wang; Shu-cai Li; Li-ping Li; Peng Lin; Zhen-hao Xu; Cheng-lu Gao (Bulletin of Engineering Geology and the Environment, 2019)

Landslide integrated characteristics and susceptibility assessment in Rongxian county of Guangxi, China - Li-ping Liao; Ying-yan Zhu; Yan-lin Zhao; Hai-tao Wen; Yun-chuan Yang; Li-hua Chen; Shao-kun Ma; Ying-zi Xu (Journal of Mountain Science, 2019)

Numerical assessments of recharge-dominated groundwater flow and transport in the nearshore reclamation area in western Taiwan - Chuen-Fa Ni; Wei-Ci Li; Shaohua Marko Hsu; I-Hsien Lee; Chi-Ping Lin (Environmental Monitoring and Assessment, 2019)

Programmed cell death induced by cadmium stress and/or boron deprivation in tobacco (Nicotiana tabacum L.) cultivar Bright Yellow 2 cells - Li Ping Jiang; Lin Zi; Xiao Fang Liu; Zi-Xi Liu; Lai Fu Zhong; Xiang Xin Xue (In Vitro Cellular & Developmental Biology - Plant, 2019)

Plantlet regeneration from primary callus cultures of Lilium brownii F.E.Br. ex Miellez var. giganteum G. Y. Li & Z. H. Chen, a rare bulbous germplasm - Yun Wu; Yi-Di Ma; Yue Li; Lin Zhang; Yi-Ping Xia (In Vitro Cellular & Developmental Biology - Plant, 2019)